Controlling model of dispersed leachate in the landfill site of Tamangapa Makassar Indonesia - Badaruddin, Sugiarto (Politeknik Negeri Ujung Pandang, 2023)
The Tamangapa landfill, the only operational landfill in Makassar City since 1995, is the subject of this study. The objective is to determine the direction of leachate flow generated by the waste in the Tamangapa landfill and simulate remediation management for the dispersed leachate, which has contaminated the groundwater flowing into community wells. Modflow + MT3DMS software was employed to model the groundwater flow direction, leachate dispersion, and pumping simulations. The concentrations of interest in this research were iron (Fe) and manganese (Mn). The modeling results revealed that the leachate from the Tamangapa landfill spreads from northwest to southeast, following the groundwater flow direction, and contaminates the community wells. Subsequently, a remediation management plan was developed using modeling techniques, specifically through pumping simulations with a pumping rate of 1500 m3/day. This pumping process was conducted until all the contaminated leachate in the community wells was removed, which was estimated to require a pumping duration of 15 months.